Organizational isomorphism and property investment decision-making amidst disruptions: evidence from listed property trusts in New Zealand - Bolomope, Muhammed; Amidu, Abdul-Rasheed; Levy, Deborah; Filippova, Olga (International Journal of Strategic Property Management, 2022)
This paper explores the extent of organizational isomorphism (homogeneity and resemblances) in the disruption-driven investment decision-making strategies of Listed Property Trusts (LPTs) in New Zealand. Based on the tenets of institutional theory, this article conceptualizes LPTs as organizations within an investment environment, comprising several firms and actors that are bounded by formal and informal rules. By exploring the interactions and interdependencies across organizational hierarchies in the investment environment, this study adopts a phenomenological approach within case studies in clarifying the extent of homogeneity in the decision-making strategies of LPTs amidst disruptions. The research outcome suggests that LPTs demonstrate normative, coercive and mimetic isomorphic tendencies as they seek legitimacy amidst the uncertainties associated with property market disruptions. Apart from adhering to the peculiar rules and norms of property investment decision-making within their investment environment, this study reveals the tendency of LPTs to observe and replicate the responsive actions of similar organizations as they adjust to market uncertainties. Therefore, the research outcome provides a clearer description of the actual decision-making behaviour of LPTs amidst market disruptions and how subjective behavioural tendencies could evolve to become a legitimate standard of reasoning amongst LPTs.